Ceropegia chuakulii sp. nov. (Asclepiadoideae, Apocynaceae) from eastern Thailand - Kidyoo, Manit; Kidyoo, Aroonrat (Phytotaxa, 2019)
Ceropegia chuakulii is a new species from eastern Thailand. Illustrations, photographs and comparison of diagnostic characters to the morphologically similar species, C. acicularis Kidyoo are provided. These two species are characterized by erect stems, needle-like leaves, one–flowered sessile inflorescences and spathulate corolla lobes that are connate at tips. Ceropegia chuakulii is, however, clearly distinguished from C. acicularis by its ovoid to globose corolla tube, corolla lobes being as long as corolla tube, deeply bifid interstamial corona lobes with triangular-lanceolate segments. In addition, the analyses of quantitative morphological traits of flowers also strongly supported the distinctiveness of the new species.